PEMANFAATAN TUMBUHAN DALAM PROSES PEWARNAAN KAIN TENUN IKAT DI PULAU NDAO, DESA NDAO NUSE, KABUPATEN ROTE NDAO - Delfi Yulianti Ledoh; Alan Ch Sabuna; Yanti Daud (Prodi Pendidikan Biologi FKIP Universitas Kristen Artha Wacana, 2021)
ABSTRACT This study aims to determine the types of natural coloring plants, organs plant or parts used, the processing to the colors produced from plants organs used in the process of coloring woven cloth on Ndao Island, Ndao Nuse Village, Ndao Nuse sub-district, Rote Ndao Regency. The method used is a qualitative descriptive method. The technique used in this study is direct observation techniques in the field and semi-structured interviews. Semi-structured interviews are interview processes that use interview guides derived from the development of topics and ask questions to ikat weaving craftsmen, the aim is to explore and obtain information related to the data needed. Based on the results of research in Ndao Nuse Village, Ndao Nuse sub-district, Rote Ndao Regency, found 5 types of natural coloring plants that are utilized by the Ndao Nuse community in the process of coloring woven cloth, namely tarum (Indigofera tinctoria L) producing black, turmeric rhizome (Curcuma domestica L) producing yellow, legundi (Vitex trifolia L) produces a light yellow color, kedondong fence (Lannea nigratana) produces a brown color, the green color is produced red distance (Jatrhopa gossiphofolia). Parts or organs of plants used are leaves, rhizomes and bark. The process of processing plant parts or organs that are used to produce color includes collision, boiling, and soaking. In addition to the 5 types of plants that are used as basic dyes there are also plants and other additives used in the coloring process are lime, whiting, and alum. The benefits of this additional material are as a color enhancer so that the color produced does not fade easily. Most of the plants that have potential as natural dyes for connective weaving have been cultivated. Plants that are cultivated are tarum, turmeric, and kedondong fence. Keywords: Weaving, Natural Staining Plants ABSTRACTThis study aims to determine the types of natural coloring plants, organs plant or parts used, the processing to the colors produced from plants organs used in the process of coloring woven cloth on Ndao Island, Ndao Nuse Village, Ndao Nuse sub-district, Rote Ndao Regency. The method used is a qualitative descriptive method. The technique used in this study is direct observation techniques in the field and semi-structured interviews. Semi-structured interviews are interview processes that use interview guides derived from the development of topics and ask questions to ikat weaving craftsmen, the aim is to explore and obtain information related to the data needed. Based on the results of research in Ndao Nuse Village, Ndao Nuse sub-district, Rote Ndao Regency, found 5 types of natural coloring plants that are utilized by the Ndao Nuse community in the process of coloring woven cloth, namely tarum (Indigofera tinctoria L) producing black, turmeric rhizome (Curcuma domestica L) producing yellow, legundi (Vitex trifolia L) produces a light yellow color, kedondong fence (Lannea nigratana) produces a brown color, the green color is produced red distance (Jatrhopa gossiphofolia). Parts or organs of plants used are leaves, rhizomes and bark. The process of processing plant parts or organs that are used to produce color includes collision, boiling, and soaking. In addition to the 5 types of plants that are used as basic dyes there are also plants and other additives used in the coloring process are lime, whiting, and alum. The benefits of this additional material are as a color enhancer so that the color produced does not fade easily. Most of the plants that have potential as natural dyes for connective weaving have been cultivated. Plants that are cultivated are tarum, turmeric, and kedondong fence. Keywords: Weaving, Natural Staining Plants